1996
DOI: 10.1093/nar/24.16.3173
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of oligoribonucleotides containing 4-thiouridine using Fpmp chemistry. Photo-crosslinking to RNA binding proteins using 350 nm irradiation

Abstract: The preparation of a 4-thiouridine phosphoramidite suitable for RNA synthesis and its subsequent incorporation into oligoribonucleotides is described. The thiol group is protected with a 2-cyanoethyl group and the 2'-OH with a 1-(2-fluorophenyl)-4-methoxypiperidin-4-yl function. Thiouridine-containing oligoribonucleotides were used as 350 nm UV crosslinking probes for the photoaffinity labelling of RNA binding proteins. Specific crosslinking was demonstrated between the Rev protein of HIV-1 (as a glutathione S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Alternatively, RNA containing a reactive chemical group at the 5Ј or 3Ј terminus is generated by in vitro transcription, followed by the coupling of photochemical probe to RNA via the reactive moiety (Burgin and Pace 1990;Fidanza et al 1994). Additionally, a limited number of photoactivatable nucleotide analogs can also be incorporated into RNA by chemical synthesis (Shah et al 1994;McGregor et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, RNA containing a reactive chemical group at the 5Ј or 3Ј terminus is generated by in vitro transcription, followed by the coupling of photochemical probe to RNA via the reactive moiety (Burgin and Pace 1990;Fidanza et al 1994). Additionally, a limited number of photoactivatable nucleotide analogs can also be incorporated into RNA by chemical synthesis (Shah et al 1994;McGregor et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…UV Cross-linking of MetJ Repressor with RNA Containing 4-Thiouridine-Cross-linking of the MetJ repressor to RNA containing 4-thiouridine was carried out as described previously (26). Samples contain-…”
Section: Methodsmentioning
confidence: 99%
“…Photocross-linking of 4-Thiouridine-containing RNA to MetJ-It has previously been shown that both oligodeoxyribonucleotides containing 4-thiothymidine and oligoribonucleotides containing 4-thiouridine can be used to photocross-link DNA-and RNA-binding proteins (26,34). We had hoped to use this approach to map the regions of MetJ in contact with the RNA ligand.…”
Section: Analysis Of a Rna-metj Repressor Complexmentioning
confidence: 99%
“…The chemical synthesis of oligodeoxy-and oligoribonucleotides containing 4-thiopyrimidine and 6-thiodeoxyguanosine requires special protection of the sulfhydryl group (267,270). The EcoRV restriction endonuclease and modification methylase have been investigated with oligonucleotides containing these analogs (267).…”
Section: Photoaffinity Cross-linkingmentioning
confidence: 99%